Authentic Assessment in the Subject of Islamic Religious Education and Character Education under the 2013 Curriculum - Musyafangah; Isnaeni, Ida Farida (Indonesian Academy of Social and Religious Research (IASRR), 2025)
Authentic assessment in the 2013 Curriculum is one of the key components aimed at comprehensively evaluating students' competencies, including cognitive, affective, and psychomotor aspects. Although it aims to provide a more realistic portrayal of students' abilities, this assessment model is often considered burdensome by teachers, particularly in terms of time, instrument preparation, and the complexity of the assessment techniques. This study aims to explore the implementation of authentic assessment in the subjects of Islamic Religious Education and Character Education at SMP Negeri 1 Purwokerto, a pilot school for the 2013 Curriculum. The study adopts a qualitative approach with a descriptive method, gathering data through interviews, observations, and documentation. The results show that authentic assessment at SMP Negeri 1 Purwokerto is carried out systematically through planning, implementation, and reporting stages. In the planning stage, teachers develop lesson plans that include indicators and assessment instruments aligned with the competencies to be achieved. In the implementation stage, assessments are conducted using various techniques such as observation, assignments, and practical exercises, tailored to the characteristics of the material. Reporting of assessment results is done both manually and electronically through the e-Rapor application. This study provides a deeper understanding of the challenges and solutions in the implementation of authentic assessment, as well as its implications for teachers and schools in implementing the 2013 Curriculum.